OS1.6 Characterizing the Over-expression of Yki/YAP/TAZ Transcription Factors in Gliomagenesis and Results of a Phase 0 Clinical Trial for a Proposed Novel Treatment of Glioblastomas. (19th September 2018) - Vigneswaran, K; Oh, S; Lallani, S; Read, R; Olson, J
Abstract: Background: Glioblastomas (GBMs) harbor frequent genetic lesions that include amplification, mutation, and/or over expression of receptor tyrosine kinases (RTKs). Using a novel kinome wide RNAi screen we identified the Hippo kinase pathway and it downstream targets, Yki-YAP/TAZ transcription factors, as tumor enhancers in gliomagenesis. YAP/TAZ promote the initiation and progression of other tumor types and several published studies show that pharmacologic inhibition of YAP and TAZ with the drug verteporfin (VP) blocks tumor cell growth. Thus, we hypothesize that, because of RTK mutations, YAP/TAZ become overexpressed and activated to constitutively drive a TEAD-dependent gene expression program that provokes an uncontrolled expansion of RTK-PI3K mutant neural stem/progenitor cells to create malignant glial tumors. Material and Methods: We tested VP in vitro on genotyped neurosphere cultures which were assessed for self-renewal, proliferation, and survival using neurosphere formation and WST-1 assays. To confirm that VP inhibits expression of YAP/TAZ-TEAD transcriptional targets, we performed experiments and harvested RNA for RNAseq, qPCR, and completed western blots and ChIP analysis. In-vivo experiments were carried out in murine xenografts bearing YAP/TAZ-expressing GBM that were used to make organotypic slice cultures which were treated with VP and assayed for tumor growth and cell survival. A Phase 0 clinical trial was designed to determine VP bioavailability. Because VP has virtually the same excitation and emission spectra as protoporphyrin IX, we administered VP to patients prior to surgery and used fluorescence-assisted microscopy to determine if VP is visible in tumors. On encountering tumor intraoperatively, the operative microscopy system was used to illuminate the tumor bed with blue light (400–410 nm), and photographs were taken through the microscope using a camera adapted for imaging in the red (620–700 nm) emissions spectrum. Resected tumor tissue remaining after satisfying clinical goals was sent for ex vivo research analysis. Results: Our data reveal that YAP and TAZ become overexpressed in tumor cells with RTK mutations, and that YAP/TAZ drive brain tumor cell growth and progression by up-regulation of novel RTK genes including EGFR. VP treatment knocks down target gene transcription, protein levels, leads to cell death and halts tumor progression. VP extraction from tumor tissue and fluoroscopic examination show successful drug uptake from all patients in a Phase 0 clinical trial. Conclusion: We believe that as a consequence of RTK mutations, YAP/TAZ becomes over-expressed in gliomas and constitutively drive a TEAD-dependent gene expression program that provokes an uncontrolled expansion of RTK -PI3K mutant neural stem/progenitor cells to create malignant glial tumors that can be treated with VP which shows bioavailability in glioblastomas.